2010
DOI: 10.1038/cdd.2010.67
|View full text |Cite
|
Sign up to set email alerts
|

p22phox-dependent NADPH oxidase activity is required for megakaryocytic differentiation

Abstract: Transient reactive oxygen species (ROS) production is currently proving to be an important mechanism in the regulation of intracellular signalling, but reports showing the involvement of ROS in important biological processes, such as cell differentiation, are scarce. In this study, we show for the first time that ROS production is required for megakaryocytic differentiation in K562 and HEL cell lines and also in human CD34 þ cells. ROS production is transiently activated during megakaryocytic differentiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 37 publications
4
95
1
1
Order By: Relevance
“…Interestingly, pre-treating monocytes with the antioxidant butylated hydroxyanisole (BHA) prior to differentiation inhibits M2 but not M1 polarization, as indicated by analysis of macrophage differentiation markers and M1/M2 polarization markers. The authors attribute this to the effects of BHA, i.e., block of ROS production, in inhibiting ERK activation during macrophage differentiation, consistent with previous reports implicating a role for ROS as well as MAP kinases in macrophage differentiation [5]. Furthermore, LPS and IFN-γ but not IL-4 stimulation can "rescue" ERK activation, perhaps in a manner dependent on ROS production, thus explaining why M2 but not M1 polarization is impaired by antioxidant treatment (Figure 1).…”
supporting
confidence: 86%
“…Interestingly, pre-treating monocytes with the antioxidant butylated hydroxyanisole (BHA) prior to differentiation inhibits M2 but not M1 polarization, as indicated by analysis of macrophage differentiation markers and M1/M2 polarization markers. The authors attribute this to the effects of BHA, i.e., block of ROS production, in inhibiting ERK activation during macrophage differentiation, consistent with previous reports implicating a role for ROS as well as MAP kinases in macrophage differentiation [5]. Furthermore, LPS and IFN-γ but not IL-4 stimulation can "rescue" ERK activation, perhaps in a manner dependent on ROS production, thus explaining why M2 but not M1 polarization is impaired by antioxidant treatment (Figure 1).…”
supporting
confidence: 86%
“…Previous data have established that p22 hox -dependent NADPH oxidase activity is responsible for ROS production and required for MK differentiation. 32 Despite the importance of ROS signaling in cell quiescence and lineage fate, 33 there are no identified ROS-regulating mutations that modulate human platelet counts, and we would speculate that the temporally restricted nature of BLVRB-associated ROS priming provides the developmentally regulated signal for accelerated MK differentiation. Using a bilineage model of erythro/megakaryocytopoiesis, we saw no evidence for MK lineage partitioning, most consistent with a model of postcommitment megakaryocytopoiesis and not altered E/Meg lineage balance.…”
Section: Discussionmentioning
confidence: 95%
“…16,17 Accordingly, we hypothesized that defective BLVRB S111L redox coupling could affect ROS accumulation, a requisite upstream signaling messenger of MK differentiation, 31,32 and stem cell quiescence during migration from hypoxic (low ROS) osteoblastic to oxygen-rich (high ROS) vascular niches. 33,34 Hematopoietic-derived (CD34 1 ) iPSCs infected with individual lentiviruses established that iPSC/BLVRB WT cells (expressing BLVRB approximately twofold greater than control) retained enhanced redox activity (P 5 .001) compared with both control and iPSC/BLVRB S111L cells; redox coupling in iPSC/BLVRB S111L paralleled that of control iPSCs ( Figure 5A).…”
Section: Blvrb Redox Function Alters Cellular Ros Accumulationmentioning
confidence: 99%
“…[65][66][67][68][69] However, it is now accepted that ROS may have an important role in regulating signal transduction pathways, gene expression and differentiation, although the molecular mechanisms upstream and downstream ROS generation are not fully understood. [70][71][72][73][74][75] The main nonmitochondrial sources of ROS are the NADPH oxidases, which are membrane-associated multi-protein complexes, of which NFC2/p67phox is an essential and crucial component, which produce superoxide. In this study, we identified NCF2 gene as a novel p53 target.…”
Section: Discussionmentioning
confidence: 99%